Prinzipien moderner Technologiepolitik - Georg Erber (Deutsches Institut für Wirtschaftsforschung (DIW), 1998)
– During the last decade a number of principles of modern technology policy emerged from the intensive debate on efficient designs of technology policy to encourage and strengthen the competitiveness of economies. While at the beginning national innovation systems like national economies seemed to be a sufficient framework the ongoing process of globalization of knowledge production and its rapid diffusion changed the perspective. However, each country as a distinct location in a global economy and in an emerging global innovation system has to develop its particular competence to become or remain an attractive partner. A number of principles should be applied as guide lines to design and evaluate the respective technology policy. Nine principles are proposed in the paper. Starting with the destinction of mission versus diffusion oriented technology policies one objective of modern technology policy is to search for an adequate policy mix. Next the concept of network development in innovation systems looks for ways to increase the efficiency of the innovation system. Each institution of the innovation system should become part of a competence centre which link research institutions with innovative companies and government agencies involved in the funding and regulation process of innovation, forming something like a triple helix, a term proposed by Leydesdorff. Competence centres link to each other in the innovation system and compete with others to win market shares in the innovation system. Furthermore each organisation should apply internally and externally the principles of learning with those of lean research organisations. The basic framework, however, to ensure efficiency in the innovation system is that the government establishes a legal and regulatory framework to foster institutional competition in the innovation system so that inefficient institutions are replaced by efficient ones through a self-selection process. Selection might be accomplished by a market mechanism or a continuous evaluation of institutions. Without sufficient scientific reputation or market success no institution should be entitled to permanent funding from public or private sources. The theoretical perfect split of public and private financing would be given by the difference between the private and social rate of return of an innovation activity, so that only the amount of positive externalities which cannot be internalised by private sources should be financed by public ones. Furthermore [...]
Keywords: O38; 330; Forschungs- und Technologiepolitik